Handbook of distance education - Moore, Michael G. (New York : Routledge, 2013)
'The third edition of this award-winning handbook continues the mission of its predecessors: to provide a comprehensive compendium of research in all aspects of distance education, arguably the most significant development in education over the past three decades. While the book deals with education that uses technology, the focus is on teaching and learning and how its management can be facilitated through technology. Key features include:Comprehensive coverage that includes all aspects of distance education, including design, instruction, management, policy, and a section on different audiences.Chapter authors frame their topic in terms of empirical research (past and present) and discuss the nature of current practice in terms of that research. Future research needs are discussed in relation to both confirmed practice and recent changes in the field.Section one provides a unique review of the theories that support distance education pedagogy. Section six provides a unique review of distance education as a component of a global culture. This book will be of interest to anyone engaged in distance education at either the K-12 or college level. It is also appropriate for corporate and government trainers and for administrators and policy makers in all these environments'--
Includes bibliographical references and index.
Keywords: Distance education -- Handbooks, manuals, etc